Correction: Corrigendum: Emerging roles of ARHGAP33 in intracellular trafficking of TrkB and pathophysiology of neuropsychiatric disorders - Takanobu Nakazawa (Nature Portfolio, 2016)
Nature Communications 7: Article number:10594 (2016); Published: 03 February 2016; Updated: 20 April 2016 Previous work by Rosário et al. 2007 and Schuster et al. 2015 describing the role of ARHGAP33 in regulating dendrite and dendritic spine development, as well as neuropsychiatric disorder-relatedbehaviours in developing and adult mice, was inadvertently omitted from the reference list of this Article and should have been cited as follows.